Breastfeeding is Best. But What After Breastfeeding? - Yvan Vandenplas; Hegar Badriul; Ray Wagiu Basrowi (Indonesian Nutrition Association, 2019)
Long-term exclusive breastfeeding is definitively the best feeding for every infant. Exclusive breast feeding should be for six months. From the age of six months onwards, solid food should be introduced while breast feeding is continued.1There are only very few contra-indications for breast feeding or mother’s milk. A maternal severe disease is an example of a contra-indication for breast feeding. If a mother has to take medication or undergo a treatment that may have a deleterious effect on the health of the baby, such as chemotherapy or radiotherapy, breast feeding cannot be recommended.2In such a situation, mother’s milk from a different mother or a “milk bank” may offer a solution. If this are not possible, infant formula is indicated. Some seldom metabolic diseases such as galactosemia are also contra-indications for mother’s milk, because in such a situation lactose is causing severe damage to the baby. Cow’s milk based lactose containing infant formula is then as well contra-indicated, since the baby cannot metabolize lactose. However, it speaks for itself that these situation are exceptional.3,4